Membangun Semangat Mahasiswa Pascasarjana Iain Madura Dalam Mata Kuliah Filsafat dan Pemikiran Pendidikan Islam (Fokus: Penerapan Strategi Pembelajaran Interaktif MBKM) - Mulyadi; Inayati, Mahfida (Al Qodiri : Jurnal Pendidikan, Sosial dan Keagamaan, 2023)
Learning today must have a good strategy to foster student participation in the learning process. So that learners are interested in the learning process. Problems that occur in the field many students who take part in learning are not on time, then there are some technical problems that interfere with learning The problem that often occurs is that there are several indicators behind but the desire and desire of each student will encourage success. The research method uses a qualitative approach with a descriptive type. The informants involved in this research were some students of Iain Madura, Podi Pai Postgraduate and lecturers who taught Islamic philosophy and education thoughts with proposive sampling techniques. Data collection from observations, interviews and documentation. The learning process used is blended learning found in the MBKM curriculum with interactive learning strategies. The learning process on the material of philosophy and thought of Islamic education is more effective or more comfortable to be carried out offline or face-to-face because the activeness of students is clearly felt. So that everything that becomes an obstacle can be overcome quickly. However, even though this learning is carried out online in accordance with the results of data exposure, it does not reduce the enthusiasm of students to always be active in the implementation of learning.